High-Precision Angle Measurement for Position Control in Industrial Drives Systems with Shaft Resolver - Çelikel, Reşat; Gundogdu, Ahmet (My University, 2024)
Resolver is a shaft angle sensor, which is mechanically connected to the motor shaft and operates according to the induction principle. A high frequency sinusoidal signal is applied to its input and produces two signals in the form of sine and cosine at its output. The output signals include the angle information of the motor shaft. Using these signals, the shaft angle of the motor is determined. In the study, a sinusoidal signal at the 5 kHz frequency was applied to an input resolver as the conventional method. After, the fact that applied to two PWM signals which has a duty ratio d=0.5 at 20 kHz and 100 kHz frequency is proposed as different from the conventional method. These PWM signals are the input signals of the resolver. Thus, complex equipment will not be needed to produce the high frequency sinusoidal signal. With only a simple amplifier circuit, a high frequency input signal will be produced. More sensitive angle information will be obtained with high frequency stimulation. A simulation study of conventional and proposed methods has been performed in MATLAB/Simscape environment. As a result of the simulation study, the information on the motor angle obtained from both methods was compared by using figures and details. By increasing the applied PWM signal from 20 kHz to 100 kHz, measurement errors related to shaft angle change were minimized and more precise position information was obtained.
Keywords: Position Control; Robotic; Shaft Resolver; Industrial Drives